The Role of International Organizations in the Development and Advancement of International Law: A Case Study of UN and EU: https://doi.org/10.55966/assaj.2025.4.1.038 - Dr. Tahira Mumtaz; Dr. Ammara Tariq Cheema; Imman Batool (`, 2025)
By creating and upholding global values and standards, international organizations play a vital role in the development of international law. This research paper examines the role of the United Nations (UN) amd EU, prominent international institutions, in establishing and enforcing international law. Specialized UN agencies such as the International Court of Justice (ICJ), the United Nations General Assembly (UNGA), and the International Law Commission (ILC) have played a significant role in the development, codification, and implementation of international law. The European Union operates on the principle of upholding and ensuring this right, and respect for international law is one of its main goals. In addition to the norms of international law that the European Court of Justice disagrees with, the Union guarantees these values. The development of the international legal order is influenced by its involvement in treaty-making, its impact on customary law, and its involvement in dispute resolution. In order to settle conflicts and expand its global role, the Union has strengthened and established an appropriate institutional and legal framework. The United Nations and European Union collaborate with other regional and international organisations, promote ongoing communication, identify emerging issues, and provide dispute resolution mechanisms. However, this research also acknowledges the UN’s and EU’s inherent flaws and challenges. It explores reform proposals to address these issues, strengthen the organization’s authority, and more effectively achieve its primary objectives. By critically analyzing the UN’s and EU’s role and impact on international law, this article aims to shed insight into how international organizations function and how they influence international legal standards. Keywords: International institutions, International courts, impacts, Unions.